Inspiring workplace spirituality - Neal, Judi (The future of work, 2023)
Conventional measurements of knowledge are usually based on tangible qualitative and quantitative research, where progress is manifested incrementally with little visible impact. Though workplace challenges are rarely examined from a spiritual perspective, both experience and research efforts have shown that this vein of thinking can deepen personal intuition and provide real breakthroughs and transformations for those who might otherwise feel stuck in their work environment or wider career. Drawing on author Judi Neal's wealth of experiences and observations, Inspiring Workplace Spirituality invites deeper reflections on the profound questions and issues that conventional forms of knowledge often fail to encompass. Providing specific practices and tools for applying internal spirituality on a day-to-day level, Neal proposes seeing work as sacred. Sharing accessible stories and examples, she explores the importance of spiritual values such as gratitude, compassion, and forgiveness within the workplace. Channelling new ways of perceiving and responding to everyday challenges, Inspiring Workplace Spirituality acts as a unique guide for professionals who are ready to elevate their internal leadership journey and assume the presence and self-awareness that will enable them to make a positive impact wherever they work.